Controlling the Quality of Laser Sintered Parts Along the Process Chain - Rüsenberg, Stefan; Weiffen, R.; Knoop, F.; Schmid, Hans-Joachim (23rd Annual International Solid Freeform Fabrication Symposium)
The quality of laser sintered parts, in this work, manufactured by polymer laser sintering by using an EOSINT P395 Laser Sintering system, depends on several steps along the process chain. The first step is the characterization of the powder quality, whereas the rheological and physical investigations of nylon 12 powder are shown. By changing some important influencing factors, for example the powder ratio, the powder ageing and the moisture content, the influence on mechanical and physical properties, density and porosity, are investigated. The composition of the used powder is known. The previous process (storage conditions, etc.) as well as the laser sintering process (regarding energy density, temperature, etc.) is kept constant for the duration of this work. Regarding the post process in this work the cooling down phase is investigated as well. With an automatically blasting system it is possible to keep the post process parameters blasting distance and blasting time, constant. All of the tests will be performed using dry and conditioned test specimens. This work is showing the dependence on mechanical, rheological and physical parameters by varying important influencing factors along the laser sintering process quality chain.